(untitled) (Jurnal Pembangunan Sosial, 2015)
Correct attitudes and substantive courses of action are two primary factors in the process of preventing or advocating for child maltreatment cases. School teachers are among signifcant adults to children. Hence this study explores the relationships between attitudes and courses of actions of school teachers towards issues of child maltreatment. Two-hundred and ffty fve teachers participated in this study by responding to the â€œEducator and Child Abuse Questionnaireâ€. The fndings show that most of the teachers (63%) displayed uncertain attitudes regarding the issues of maltreatment. All of the teachers chose to take at least one action, rational action, when facing suspected maltreatment cases. However, Chi-Square analyses show that there are no signifcant relationships between teachersâ€™ attitudes and their courses of action. Having positive attitudes does not warrant a correct course of action. As a result, an individualâ€™s course of action is mostly affected by the uniqueness of the case and the availability of substantive information of the case.